The role of breastfeeding in breast cancer prevention: a literature review - Chen, Yulong; Jiang, Pengli; Geng, Yongqin (Frontiers in Oncology, 2023)
Breast cancer stands as the most prevalent malignancy globally. Despite the array of treatment options, its mortality rate continues to rise annually. Thus, reevaluation of factors directly linked to breast cancer emergence is imperative, alongside the development of more effective preventive measures. Estrogen levels, profoundly tied to reproduction, play a pivotal role in breast cancer development. Speculation centers on the potential of breastfeeding to mitigate cancer risk in women. However, the precise mechanism remains elusive. Breastfeeding is a modifiable reproductive factor extensively studied. Studies highlight a direct connection between lack of breastfeeding and breast cancer emergence, potentially linked to DNA methyltransferase expression alteration, aberrant methylation levels, pregnancy-associated plasma protein-A, cellular microenvironment, and oncogenes. This study reviews recent mechanisms underlying breastfeeding's role in reducing breast cancer incidence.